Microbiota composition-based donor selection affects FMT efficacy in a murine colitis model - Dai, Zhongming; Cheng, Wen; Peng, Huan; Qiu, Xiaokui; Sun, Jiawen; Liu, Xiaoqiang; Sun, Xianjiu; Cai, Jinwei; Wang, Jincui; Li, Guolong; Lv, Yongling; Chen, Shaobo; et al. (Frontiers in Immunology, 2025)
BackgroundGrowing evidence links gut microbial dysbiosis to inflammatory bowel disease (IBD) pathogenesis, establishing fecal microbiota transplantation (FMT) as a microbiota-targeted therapy; however, variable outcomes in randomized trials highlight the need to identify compositional features of donor microbiota associated with FMT efficacy.ObjectiveThis study aimed to investigate how the composition of the donor gut microbiota influences the therapeutic efficacy of FMT in IBD.MethodFecal DNA from 39 IBD patients and 42 healthy donors was analyzed via 16S rRNA sequencing. Donor-enriched genera (identified through differential analysis and median abundance thresholds) guided FMT selection. Dextran sulfate sodium (DSS)-induced colitis mice received donor microbiota transplants; disease activity and microbiota dynamics were evaluated through longitudinal sequencing.ResultsIBD patients showed reduced microbial diversity and increased Proteobacteria phylum versus healthy donors, as well as the genera Escherichia-Shigella, Megamonas, and Klebsiella. Linear discriminant analysis effect size (LEfSe) analysis identified 50 differentially abundant genera, with 36 beneficial taxa enriched in donors. Based on median abundance of these health-associated genera, four high- and low-abundance donors were selected. FMT from high-abundance donors outperformed low-abundance donors and 5-ASA in colitis mice, restoring microbial diversity to healthy levels. Recipient mice showed increased Firmicutes and Bacteroidota and decreased Verrucomicrobiota, with Lactobacillus and Dubosiella enrichment and normalization of Lachnospiraceae NK4A136 group, Akkermansia, Turicibacter, and Parabacteroides. LEfSe identified 24 genera distinguishing IBD and control mice; post-FMT microbiota of high-abundance donor recipients more closely resembled controls, correlating with therapeutic success.ConclusionFMT ameliorated IBD symptoms in murine models, with therapeutic efficacy associated with the relative abundance of health-associated microbial genera in donor microbiota.